Identification of the key structural elements of a dihydropyrimidinone core driving toward more potent Hsp90 C-terminal inhibitors. Issue 87 (12th October 2016) - Teracciano, S.; Chini, M. G.; Vaccaro, M. C.; Strocchia, M.; Foglia, A.; Vassallo, A.; Saturnino, C.; Riccio, R.; Bifulco, G.; Bruno, I.
Abstract : Dramatic improvement in the biological activity of DHPM derivatives as a new class of Hsp90 C-terminal inhibitors for cancer therapy. Abstract : Hsp90 C-terminal modulation represents an attractive strategy for the development of potent and safer antitumor compounds. Continuing our investigation on DHPM type inhibitors here we report a new set of potent C-terminal ligands which allowed us to identify the key structural features crucial for the biological activity.